The Relationship between Natural Resource Abundance and Human Development in Belt and Road Initiative Countries: The Role of Financial Development - Salahodjaev, Raufhon; Djalilov, Bekhzod; Bakieva, Iroda; Kobiljonov, Islomjon (International Journal of Energy Economics and Policy, 2024)
The goal of this study is to explore the relationship between natural resource abundance and human development. In particular, account for the role of financial development. This study uses data from 51 BRI countries over the period 2000-2018. Concerning the HDI, the results suggest U-shaped relationship between total natural resource rents and HDI. Similarly, gas rents, mineral rents and oil rents are non-linearly related to HDI in BRI countries. For example, in the case of total rents, once its share in GDP exceeds 42.8%, further dependence on natural resources leads to increase in HDI. In our sample, only Iraq, Kuwait, Saudi Arabia and Oman were above the turning points at some observation years. The interaction term is positive and significant. This implies that increase in natural resource rents in countries with higher levels of financial development does not lead to a reduction of human development. In a similar vein, domestic credit to private sector alleviates negative effect of oil and mineral rents.